Separator and device including same
By designing a multi-layer separation membrane with high heat shrinkage, thermal perforation and high temperature box characteristics, the safety problems of secondary batteries when used in extreme environments in the prior art are solved, and higher thermal stability and mechanical strength are achieved.
Patent Information
- Application Number
- JP2024562884
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2022-04-24
- Publication Date
- 2025-05-09
AI Technical Summary
When used in extreme environments (such as collisions, studs and high temperature environments), it is difficult to ensure safety, which can easily lead to safety problems such as explosions.
An improved separation membrane was designed with a multilayer structure with high heat shrinkage, heat perforation and high temperature box characteristics, including a porous matrix and a porous coating consisting of inorganic particles and a metal-containing adhesive that was treated with high temperature heat perforation.
Improves battery safety, enhances thermal stability and mechanical strength, and reduces the risk of short circuits and the possibility of thermal runaway in extreme environments.
Smart Images

Figure 2025514841000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to the technical field of energy storage, and more particularly to a separator and a device including the same. [Background technology]
[0002] Rechargeable secondary batteries are considered one of the most attractive energy storage systems due to their advantages of high energy density, relatively simple reaction mechanism, high operating voltage, long life, environmental friendliness, etc. Currently, secondary batteries are widely used in various fields such as wearable devices, smartphones, drones, and laptops.
[0003] As secondary batteries are widely used in various fields, people's demand for secondary batteries is increasing. However, when secondary batteries are used in some harsh environments (such as collision, nail penetration, and hot box) or abnormally used in other situations, it is difficult to ensure the safety characteristics of the battery, and the battery may even explode. In view of this, there is an urgent need to improve the safety characteristics of secondary batteries. Summary of the Invention
[0004] In order to solve at least the above problems, the present invention improves the safety characteristics of electrochemical devices by improving the separator of the electrochemical device. Specifically, the present invention provides a separator with high safety characteristics, and the separator has excellent thermal shrinkage resistance, thermal perforation resistance, and hot box resistance.
[0005] According to one aspect of the present invention, the present invention provides a separator, the separator comprising a porous substrate and a porous coating layer, the porous coating layer being provided on at least one surface of the porous substrate, the porous coating layer comprising inorganic particles and a binder, the binder comprising a first binder comprising a metal element, the separator being thermally perforated with a round-tipped needle having a diameter R and heated to 500°C to obtain a rupture hole generated in the separator, any two points on the edge of the rupture hole are connected, the distance between the two points is calculated, and the maximum value is taken as r, where R and r satisfy 400 μm≦R≦1000 μm and 0.9≦r / R≦5.
[0006] According to an embodiment of the present invention, the r satisfies 400 μm≦r≦1500 μm.
[0007] According to an embodiment of the present invention, when the compressive strength of the binder is α MPa, α satisfies 0.5≦α≦10.
[0008] According to an embodiment of the present invention, when the glass transition temperature of the binder is Tg, Tg satisfies 150°C≦Tg≦300°C.
[0009] According to an embodiment of the present invention, the metal element includes at least one of metal elements having a valence of +1, +2, or +3.
[0010] According to an embodiment of the present invention, the metal elements include at least two of the metal elements having a valence of +1, +2, or +3.
[0011] According to an embodiment of the present invention, the first binder satisfies at least one of the following: (a) the metal element having a valence of +1 includes at least one of Li and Na; (b) the metal element having a valence of +2 includes at least one of Ca and Mg; and (c) the metal element having a valence of +3 includes Al.
[0012] According to an embodiment of the present invention, the binder satisfies at least one of the following: (d) when a is a molar content ratio of the metal element having a valence of +1 to the metal element having a valence of +2, a satisfies 1≦a≦10; and (e) when b is a molar content ratio of the metal element having a valence of +1 to the metal element having a valence of +3, b satisfies 1≦b≦50.
[0013] According to an embodiment of the present invention, the first binder includes at least one of a carboxyl group and a sulfonic acid group, and when the pH value of the first binder is pH1, pH1 satisfies 7≦pH1≦11.
[0014] According to an embodiment of the present invention, the first binder includes at least one of sodium polymethylcellulose, lithium polymethylcellulose, lithium polycarboxymethylcellulose, lithium polyhydroxypropylmethylcellulose, calcium polyacrylate, lithium polyacrylate, and calcium polymethacrylate.
[0015] According to an embodiment of the present invention, the binder further comprises a second binder, and when the weight ratio of the first binder to the second binder with respect to the total weight of the porous coating layer is β, β satisfies 0.2≦β≦4.
[0016] According to an embodiment of the present invention, the second binder includes at least one of a carboxyl group and a sulfonic acid group, and when the pH value of the second binder is pH2, pH2 satisfies 3≦pH2≦7.
[0017] According to an embodiment of the present invention, the second binder includes at least one of polybutyl acrylate, polyethyl acrylate, polybutyl methacrylate, polymethyl methacrylate, and styrene butadiene rubber.
[0018] According to an embodiment of the present invention, the specific surface area of the inorganic particles is S BET m 2 / g, S BET 2≦S BET <= 10.
[0019] According to an embodiment of the present invention, the particle diameters Dv50 and Dv99 of the inorganic particles satisfy 0.3 μm≦Dv50≦3 μm and Dv99≦4 μm, respectively.
[0020] According to an embodiment of the present invention, the inorganic particles include at least one of aluminum oxide, boehmite, zirconia, boron nitride, silicon nitride, and aluminum nitride.
[0021] According to an embodiment of the present invention, the porous coating layer further comprises a wetting agent, and when the content of the inorganic particles is m1 weight %, the content of the binder is m2 weight %, and the content of the wetting agent is m3 weight %, relative to the total weight of the porous coating layer, m1, m2, and m3 satisfy 90≦m1≦96, 3≦m2≦9, 0.5≦m3≦2, and m1+m2+m3=100.
[0022] According to an embodiment of the present invention, the wetting agent includes at least one of polyoxyethylene alkylphenol ether, polyoxyethylene aliphatic alcohol ether, polyoxyethylene polyoxypropylene block copolymer, and siloxane.
[0023] According to an embodiment of the present invention, when the separator is left at 150°C for 1 hour, and compared to the initial length and width of the separator, the thermal shrinkage rate of the separator in the longitudinal direction (MD) is L1 and the thermal shrinkage rate of the separator in the transverse direction (TD) is L2, L1 and L2 satisfy L1<10%, L2<10%, and 0.75≦L1 / L2≦1.2.
[0024] According to an embodiment of the present invention, when the thickness of the porous coating layer is T μm, T satisfies 0.5≦T≦3.
[0025] According to an embodiment of the present invention, when the adhesive strength of the porous coating layer is FN / m, F satisfies 5≦F≦100.
[0026] According to another aspect of the present invention, the present invention further provides an electrochemical device comprising a separator according to any of the above embodiments of the present invention.
[0027] According to another aspect of the present invention, the present invention further provides an electronic device comprising an electrochemical device according to any of the above embodiments of the present invention. [Brief description of the drawings]
[0028] [Figure 1] FIG. 1 shows a charge-coupled device (CCD) image of a separator according to the present invention after thermal perforation with a round-tipped needle of diameter R and heated to 500°C. [Diagram 2] FIG. 2 shows a CCD image of a prior art separator after thermal drilling with a round-tipped needle of diameter R and heated to 500°C. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0029] In the following, in order to explain the embodiments of the present invention, the drawings necessary for explaining the embodiments of the present invention or the prior art will be briefly described. It is obvious that the drawings described below are only a part of the embodiments of the present invention. Those skilled in the art can still obtain drawings of other embodiments according to the structures illustrated in these drawings without making creative efforts.
[0030] Examples of the present invention will be described in detail below. The examples of the present invention should not be construed as limiting the present invention.
[0031] As used herein, the terms "comprise", "include", or "containing" are used in their open, non-limiting sense.
[0032] It should be noted that amounts, ratios, and other numerical values may be presented herein in a range format, with the understanding that such range format is used for convenience and brevity, and should be understood to include not only the numerical values explicitly specified as range limits, but also all individual numerical values or subranges contained within the range, as if each numerical value or subrange were explicitly specified.
[0033] In the detailed description and claims, a list of terms connected by the terms "one or more of," "one or more of," "at least one of," or other similar terms means any combination of the listed terms. For example, if terms A and B are listed, the phrase "at least one of A and B" means A only, B only, or A and B. In another example, if terms A, B, and C are listed, the phrase "at least one of A, B, and C" means A only, B only, C only, A and B (excluding C), A and C (excluding B), B and C (excluding A), or all of A, B, and C. Term A may include a single element or multiple elements. Term B may include a single element or multiple elements. Term C may include a single element or multiple elements.
[0034] Separator: The separator is an important component of an electrochemical device, and is located between the positive and negative electrodes of the electrochemical device to transport metal ions (e.g., lithium ions), while isolating the positive and negative electrodes and preventing short circuits. However, if used abnormally, the temperature inside the electrode assembly of the electrochemical device may rise rapidly, causing the separator to thermally shrink significantly and even melt, resulting in direct contact between the positive and negative electrodes and causing a short circuit. If a short circuit occurs, thermal runaway will occur inside the electrochemical device, which will cause safety issues such as fire and explosion.
[0035] In the prior art, oil-based separators (such as aramid high-temperature resistant separators) are generally used in electrochemical devices to improve the high-temperature resistance of the separators. However, the oil-based separators have high requirements for the production process and may cause problems such as environmental pollution. In addition, the production cost of the oil-based separators is higher than that of the aqueous separators, so the production cost of the electrochemical device increases accordingly.
[0036] Based on at least the above insight into the prior art, the present invention focuses on the research of aqueous separators, and improves the components and their content of the porous coating layer in the separator, thereby improving the thermal stability and mechanical safety properties of the separator. Specifically, the separator of the present invention includes a porous substrate and a porous coating layer, the porous coating layer being provided on at least one surface of the porous substrate, and the porous coating layer includes inorganic particles and a binder. Here, one main feature of the separator of the present invention is that the binder includes a first binder, the first binder includes a metal element, and a needle with a diameter R and a round tip heated to 500°C is used to perform thermal perforation on the separator, to obtain a rupture hole generated in the separator, any two points on the edge of the rupture hole are connected, the distance between the two points is calculated, and the maximum value is r, where R and r satisfy 400 μm≦R≦1000 μm and 0.9≦r / R≦5.
[0037] According to one embodiment of the present invention, FIG. 1 shows an image of a separator taken by a CCD camera after thermal perforation using a circular-tipped needle with a diameter of R (500 μm) and heated to 500° C. As shown in FIG. 1, after thermal perforation using a high-temperature circular-tipped needle, a rupture hole occurs in the separator, and under the observation of the CCD camera, the two most distant points on the edge of the rupture hole are found, and the distance r between these two points is calculated, where r is 451 μm. In contrast, when a similar thermal perforation measurement is performed using an aqueous separator that is commonly used in the prior art, as can be seen from FIG. 2, the area of the rupture hole in the conventional aqueous separator is large, for example, the distance between the two most distant points on the edge of the rupture hole is as high as 3088 μm. The increase in the area of the rupture hole increases the risk of contact between the positive and negative electrodes, causing an internal short circuit in the battery and resulting in thermal runaway of the battery.
[0038] In some embodiments, R may be 400 μm, 500 μm, 600 μm, 700 μm, 800 μm, 900 μm, or 1000 μm, or may be within a range consisting of any two values listed above, but is not limited to this. In some embodiments, r / R may be 0.9, 1, 1.2, 1.4, 1.6, 1.8, 2, 2.2, 2.4, 2.6, 2.8, 3, 3.2, 3.4, 3.6, 3.8, 4, 4.2, 4.4, 4.6, 4.8, or 5, or may be within a range consisting of any two values listed above, but is not limited to this. In some embodiments, R and r satisfy 1≦r / R≦1.5. In some embodiments, R and r satisfy 1≦r / R≦2.5. In some embodiments, R and r satisfy 1≦r / R≦3.5. In some embodiments, R and r satisfy 1≦r / R≦4.5.
[0039] In some embodiments, r satisfies 400 μm≦r≦1500 μm. For example, r may be, but is not limited to, 400 μm, 500 μm, 600 μm, 700 μm, 800 μm, 900 μm, 1000 μm, 1100 μm, 1200 μm, 1300 μm, 1400 μm, or 1500 μm, or within a range consisting of any two of the above values.
[0040] In some embodiments, when the compressive strength of the binder is α MPa, α satisfies 0.5≦α≦10. When the compressive strength of the binder is within the above range, the binder can not only firmly bind the dispersed inorganic particles to a network skeleton structure, but also bond and integrate the inorganic particles and the substrate, ultimately improving the compressive strength of the entire separator, making the separator more resistant to stress impact and further suppressing damage caused by impact, and further improving the thermal safety characteristics and mechanical safety characteristics of the electrochemical device. In some embodiments, α can be 0.5, 1, 2, 3, 4, 5, 6, 7, 8, 9, or 10, or can be within a range consisting of any two of the above values, but is not limited thereto.
[0041] In some embodiments, the glass transition temperature of the binder, Tg, satisfies 150° C.≦Tg≦300° C. When the glass transition temperature of the binder is within the above range, the binder is not easily softened or brittle at high temperatures, and has an appropriate strength to resist stress shock and reduce damage due to impact, thereby further improving the thermal safety characteristics and mechanical safety characteristics of the electrochemical device. In some embodiments, Tg may be, but is not limited to, 150° C., 200° C., 250° C., or 300° C., or within a range consisting of any two of the above values.
[0042] In some embodiments, the metal element in the first binder includes at least one of metal elements with a valence of +1, +2, or +3. In some embodiments, the first binder further includes at least one of a carboxyl group and a sulfonic acid group. The metal ions in the first binder can form a complex with the carboxyl group or sulfonic acid group therein to form a metallic bond, which further improves the strength (e.g., compressive strength) of the binder, enables the separator to better respond to stress shock and suppresses damage due to shock, and further improves the thermal safety properties and mechanical safety properties of the electrochemical device.
[0043] In some embodiments, the metal element in the first binder comprises at least two of the metal elements with valences of +1, +2, or +3. Compared with the case where only one metal element is included, the use of at least two different metal elements in the first binder can further improve the strength of the binder, and can further improve the separator's ability to withstand stress shock and stability at high temperatures. This may be because, compared with a single metal element, different metal elements can more easily form interpenetrating metal bonds with the carboxyl and / or sulfonic acid groups in the binder to build an interpenetrating crosslinked network structure, thereby improving the mechanical properties of the material.
[0044] In some embodiments, the metal element having a valence of +1 includes at least one of Li, Na, and K. In some embodiments, the metal element having a valence of +2 includes at least one of Ca, Mg, and Ba. In some embodiments, the metal element having a valence of +3 includes Al. In some embodiments, the first binder includes at least one of Li, Na, Ca, Mg, and Al.
[0045] In some embodiments, the first binder simultaneously contains metal elements with valences of +1 and +2, and when the molar content ratio of the metal element with valence +1 to the metal element with valence +2 is a, a satisfies 1≦a≦10. In some embodiments, a may be 1, 2, 3, 4, 5, 6, 7, 8, 9, or 10, or may be within a range consisting of any two of the above values, but is not limited thereto.
[0046] In some embodiments, the first binder simultaneously contains metal elements with valences of +1 and +3, and when the molar content ratio of the metal element with valence +1 to the metal element with valence +3 is b, b satisfies 1≦b≦50. In some embodiments, b may be 1, 10, 20, 30, 40, or 50, or may be within a range consisting of any two of the above values, but is not limited thereto.
[0047] In some embodiments, the first binder simultaneously contains metal elements with valences of +2 and +3, and when p is the molar content ratio of the metal element with valence +2 to the metal element with valence +3, p satisfies 1≦p≦10. In some embodiments, p may be 1, 2, 3, 4, 5, 6, 7, 8, 9, or 10, or may be within a range consisting of any two of the above values, but is not limited thereto.
[0048] In some embodiments, the first binder is (1) The first binder contains Li and Na simultaneously, and when the molar content ratio of Li to Na is c, c satisfies 1≦c≦8; (2) The first binder contains Li and Mg simultaneously, and when the molar content ratio of Li to Mg is d, d satisfies 2≦d≦4; (3) The first binder contains Na and Mg simultaneously, and when the molar content ratio of Na to Mg is e, e satisfies 2≦e≦4; (4) The first binder contains Li and Ca simultaneously, and when the molar content ratio of Li to Ca is f, f satisfies 2≦f≦4; (5) The first binder contains Na and Ca simultaneously, and when the molar content ratio of Na to Ca is g, g satisfies 2≦g≦4; (6) The first binder contains Li and Al simultaneously, and when the molar content ratio of Li to Al is m, m satisfies 1≦m≦20; (7) The first binder contains Na and Al simultaneously, and n, the molar content ratio of Na to Al, satisfies 1≦n≦20; Satisfy at least one of them.
[0049] In some embodiments, the pH value of the first binder can be adjusted by adjusting the content and ratio of the carboxyl group or sulfonic acid group and the metal element in the first binder. In some embodiments, when the pH value of the first binder is pH1, pH1 satisfies 7≦pH1≦11. When the pH value of the first binder is within the above range, the first binder can provide sufficient metal ions to form metal ion complex bonds with the carboxyl group or sulfonic acid group therein, thereby further improving the thermal stability and mechanical properties of the separator. In some embodiments, pH1 can be 7, 8, 9, 10, or 11, or be within a range consisting of any two of the above values, but is not limited thereto.
[0050] In some embodiments, the first binder includes at least one of, but is not limited to, sodium polymethylcellulose, lithium polymethylcellulose, lithium polycarboxymethylcellulose, lithium polyhydroxypropylmethylcellulose, calcium polyacrylate, lithium polyacrylate, and calcium polymethacrylate.
[0051] In some embodiments, when the weight content of the first binder is w1% with respect to the total weight of the porous coating layer, w1 satisfies 0.5≦w1≦4. In some embodiments, w1 may be, but is not limited to, 0.2, 0.5, 1, 1.5, 2, 2.5, 3, 3.5, or 4, or within a range consisting of any two of the above values.
[0052] In some embodiments, the first binder is a solvent-based adhesive, which is a polymeric adhesive that is dissolved in a solvent to form a solution. In some embodiments, the solvent is water.
[0053] In some embodiments, the binder includes a second binder. In some embodiments, the second binder is a different type of binder than the first binder. For example, the second binder is an emulsion type binder. An emulsion type binder is one in which a polymer adhesive is dispersed in a dispersion medium to form an emulsion. In some embodiments, the dispersion medium is water.
[0054] In some embodiments, when the weight content of the second binder is w2% based on the total weight of the porous coating layer, w2 satisfies 2.5≦w2≦5. In some embodiments, w2 may be 2.5, 3, 4, or 5, or may be within a range consisting of any two of the above values, but is not limited thereto.
[0055] In some embodiments, the second binder comprises at least one of a carboxyl group and a sulfonic acid group. When the binder comprises both the first binder and the second binder, the metal ions in the first binder can also form complexes with the carboxyl groups or sulfonic acid groups in the second binder to form metal bonds and interpenetrating network structures, thereby further improving the strength of the binder and enhancing the separator's ability to resist external force impact, thereby further improving the thermal and mechanical safety properties of the electrochemical device.
[0056] In addition, when the binder includes both the first binder and the second binder, the strength of the binder can be further improved by optimizing the weight ratio of the first binder to the second binder. In some embodiments, when the weight ratio of the first binder to the second binder (i.e., w1 / w2) is β with respect to the total weight of the porous coating layer, β satisfies 0.2≦β≦4. In some embodiments, β may be, but is not limited to, 0.2, 0.5, 1, 1.5, 2, 2.5, 3, 3.5, or 4, or within a range consisting of any two of the foregoing values.
[0057] In some embodiments, the pH value of the second binder can be adjusted by adjusting the content and ratio of carboxyl groups and / or sulfonic acid groups in the second binder. In some embodiments, when the pH value of the second binder is pH2, pH2 satisfies 3≦pH2≦7. When the pH value of the second binder is within the above range, the thermal stability and mechanical properties of the separator can be further improved. This may be because the second binder provides additional active groups (e.g., carboxyl groups or sulfonic acid groups), which can increase the probability of forming complexes with metal ions, form more metal ion complex bonds, and improve the mechanical properties of the material. In some embodiments, pH2 can be 3, 4, 5, 6, or 7, or be within a range consisting of any two values listed above, but is not limited thereto.
[0058] In some examples, the second binder includes at least one of, but is not limited to, polybutyl acrylate, polyethyl acrylate, polybutyl methacrylate, polymethyl methacrylate, and styrene butadiene rubber.
[0059] In some embodiments, the specific surface area of the inorganic particles located in the porous coating layer is S BET m 2 / g, S BET 2≦S BET In some embodiments, S BET S may be, but is not limited to, 2, 3, 4, 5, 6, 7, 8, 9, or 10, or in a range consisting of any two of the above values. BET 2≦S BET Satisfy ≦5.
[0060] In some embodiments, the particle diameter Dv50 of the inorganic particles satisfies 0.3 μm≦Dv50≦3 μm. In some embodiments, the particle diameter Dv99 of the inorganic particles satisfies Dv99≦4 μm. Here, Dv50 is also called the median diameter, and is the particle diameter when the fraction is 50% in the volume-based particle size distribution. Dv99 is the particle diameter when the fraction is 99% in the volume-based particle size distribution. When the particle diameter of the inorganic particles is in the above range, it is not only advantageous to reduce the thickness of the porous coating layer and improve the energy density of the electrochemical device, but also ensure that the adhesion site is within an appropriate range, reduce the amount of binder used, and improve the dynamic properties of the electrochemical device.
[0061] In some embodiments, inorganic particles that can be used in the separator of the present invention include, but are not limited to, at least one of aluminum oxide, boehmite, zirconia, boron nitride, silicon nitride, aluminum nitride, silica, magnesium oxide, titanium oxide, silicon carbide, aluminum hydroxide, and magnesium hydroxide.
[0062] In some embodiments, the porous coating layer further comprises a wetting agent, where the role of the wetting agent is to improve the wettability of the porous coating layer to the substrate and avoid coating leakage during the coating process. In addition, the weight percentages of the inorganic particles, binder, and wetting agent in the porous coating layer can be optimized to further improve the thermal safety properties and mechanical stability of the separator. In some embodiments, when the content of the inorganic particles is m1 wt%, the content of the binder is m2 wt%, and the content of the wetting agent is m3 wt%, relative to the total weight of the porous coating layer, m1, m2, and m3 satisfy 90≦m1≦96, 3≦m2≦9, 0.5≦m3≦2, and m1+m2+m3=100.
[0063] In some examples, the wetting agent includes at least one of, but is not limited to, polyoxyethylene alkylphenol ethers, polyoxyethylene fatty alcohol ethers, polyoxyethylene polyoxypropylene block copolymers, and siloxanes.
[0064] In some embodiments, when the separator of the present invention is left at 150° C. for 1 hour, the thermal shrinkage rate of the separator in the longitudinal direction (MD) compared to the initial length of the separator is L1, and the thermal shrinkage rate of the separator in the transverse direction (TD) compared to the initial width of the separator is L2, L1 and L2 satisfy L1<10%, L2<10%, and 0.75≦L1 / L2≦1.2. In some embodiments, L1 and L2 may be 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, or 9%, respectively, or within a range consisting of any two of the above values, but are not limited thereto. In some embodiments, L1 / L2 may be 0.8, 0.9, 1.0, 1.1, or 1.2, or within a range consisting of any two of the above values, but are not limited thereto.
[0065] In some embodiments, when the thickness of the porous coating layer is T μm, T satisfies 0.5≦T≦3. When the thickness of the porous coating layer is in the above range, the energy density of the electrochemical device can be improved and the kinetic characteristics of the electrochemical device can be improved. In some embodiments, T can be, but is not limited to, 0.5, 1, 1.5, 2, 2.5, or 3, or a range consisting of any two of the above values. Here, when the porous coating layer is applied to both sides of the porous substrate, the "thickness of the porous coating layer" refers to the sum of the thicknesses of the porous coating layers applied to both sides.
[0066] In some embodiments, when the adhesive strength of the porous coating layer is FN / m, F satisfies 5≦F≦100. When the adhesive strength of the porous coating layer is within the above range, not only is the inorganic particles firmly attached to the porous substrate and less likely to fall off, but it is also not necessary to use a large amount of binder that would degrade the dynamic properties of the electrochemical device. In some embodiments, F may be, but is not limited to, 5, 10, 20, 30, 40, 50, 60, 70, 80, 90, or 100, or within a range consisting of any two of the aforementioned values. In some embodiments, F satisfies 20≦F≦85.
[0067] In some embodiments, the porous substrate includes at least one of, but is not limited to, polyethylene (PE), ultra-high molecular weight polyethylene (UHMWPE), high density polyethylene (HDPE), polypropylene (PP), polyethylene terephthalate (PET), polyphenylene sulfide (PPS), cellulose, polyimide, polystyrene (PS), poly 4-methyl-1-pentene (TPX), polymethyl methacrylate (PMMA), polyvinylidene fluoride (PVDF), polyvinylidene fluoride-hexafluoropropylene (PVDF-HFP), polytetrafluoroethylene (PTFE), and polysulfone.
[0068] The present invention further provides an electrochemical device comprising the separator according to the above embodiments of the present invention. In some embodiments, the electrochemical device further comprises a negative electrode, a positive electrode, and an electrolyte, and the separator is located between the positive electrode and the negative electrode. Hereinafter, the present invention will be described in detail with respect to the composition of the positive electrode, the negative electrode, and the electrolyte.
[0069] Positive electrode: The positive electrode includes a positive electrode material capable of absorbing and releasing lithium (Li) (hereinafter, may be referred to as "positive electrode material capable of absorbing and releasing lithium Li"). Examples of the positive electrode material capable of absorbing and releasing lithium (Li) may include lithium cobalt oxide, lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminate, lithium manganese oxide, lithium manganese iron phosphate, lithium vanadyl phosphate, lithium vanadyl phosphate, lithium iron phosphate, lithium titanate, and lithium-rich manganese-based materials.
[0070] Specifically, the chemical formula of the lithium cobalt oxide may be:
[0071] [ka]
[0072] Here, M1 represents at least one selected from the group consisting of nickel (Ni), manganese (Mn), magnesium (Mg), aluminum (Al), boron (B), titanium (Ti), vanadium (V), chromium (Cr), iron (Fe), copper (Cu), zinc (Zn), molybdenum (Mo), tin (Sn), calcium (Ca), strontium (Sr), tungsten (W), yttrium (Y), lanthanum (La), zirconium (Zr), and silicon (Si), and the values of x1, a1, b1, and c1 are within the ranges of 0.8≦x1≦1.2, 0.8≦a1≦1, 0≦b1≦0.2, and −0.1≦c1≦0.2, respectively.
[0073] The chemical formula of the lithium nickel cobalt manganese oxide or lithium nickel cobalt aluminate may be Formula 2:
[0074] [ka]
[0075] Here, M2 represents at least one selected from the group consisting of cobalt (Co), manganese (Mn), magnesium (Mg), aluminum (Al), boron (B), titanium (Ti), vanadium (V), chromium (Cr), iron (Fe), copper (Cu), zinc (Zn), molybdenum (Mo), tin (Sn), calcium (Ca), strontium (Sr), tungsten (W), zirconium (Zr), and silicon (Si), and the values of y1, d1, e1, and f1 are within the ranges of 0.8≦y1≦1.2, 0.3≦d1≦0.98, 0.02≦e1≦0.7, and −0.1≦f1≦0.2, respectively.
[0076] The chemical formula of the lithium manganate may be Formula 3:
[0077] [ka]
[0078] Here, M3 represents at least one selected from the group consisting of cobalt (Co), nickel (Ni), magnesium (Mg), aluminum (Al), boron (B), titanium (Ti), vanadium (V), chromium (Cr), iron (Fe), copper (Cu), zinc (Zn), molybdenum (Mo), tin (Sn), calcium (Ca), strontium (Sr), and tungsten (W), and the values of z1, g1, and h1 are within the ranges of 0.8≦z1≦1.2, 0≦g<1.0, and −0.2≦h1≦0.2, respectively.
[0079] Negative electrode: The negative electrode includes a negative electrode material capable of absorbing and releasing lithium (Li) (hereinafter, may be referred to as "negative electrode material capable of absorbing and releasing lithium Li"). Examples of the negative electrode material capable of absorbing and releasing lithium (Li) may include carbon materials, metal compounds, oxides, sulfides, nitrides of lithium such as LiN3, lithium metal, metals that form alloys with lithium, and polymer materials.
[0080] Examples of carbon materials may include low graphitizable carbon, graphitizable carbon, artificial graphite, natural graphite, mesocarbon microbeads, soft carbon, hard carbon, pyrolytic carbon, coke, glassy carbon, organic polymer compound sintered body, carbon fiber, and activated carbon. Here, the coke may include pitch coke, needle coke, and petroleum coke. The organic polymer compound sintered body is a polymer material such as phenol plastic or furan resin that is carbonized by baking at an appropriate temperature, and some of them are classified as low graphitizable carbon or graphitizable carbon. Examples of polymer materials may include polyacetylene and polypyrrole.
[0081] From these anode materials capable of absorbing and releasing lithium (Li), a material with a charge / discharge voltage close to that of lithium metal is selected. This is because the lower the charge / discharge voltage of the anode material, the higher the energy density of the electrochemical device (e.g., lithium ion battery). Among them, a carbon material can be selected as the anode material because it undergoes little change in crystal structure during charging and discharging, and provides good cycle characteristics and a large charge / discharge capacity. In particular, graphite is preferred because it has a large electrochemical equivalent and can provide a high energy density.
[0082] The negative electrode material capable of absorbing and releasing lithium (Li) may include lithium metal alone, metal elements and metalloid elements capable of forming an alloy with lithium (Li), and alloys and compounds containing these elements. In particular, when used together with a carbon material, good cycle characteristics and high energy density can be obtained. The alloy used here includes alloys containing two or more metal elements, as well as alloys containing one or more metal elements and one or more metalloid elements. The alloy may be a solid solution, a eutectic crystal (eutectic mixture), an intermetallic compound, or a mixture thereof.
[0083] Examples of metal and semi-metal elements may include tin (Sn), lead (Pb), aluminum (Al), indium (In), silicon (Si), zinc (Zn), antimony (Sb), bismuth (Bi), cadmium (Cd), magnesium (Mg), boron (B), gallium (Ga), germanium (Ge), arsenic (As), silver (Ag), zirconium (Zr), yttrium (Y), and hafnium (Hf). Examples of such alloys and compounds include those having the chemical formula: s Mb t Li u and a material having the chemical formula: Ma p Mc q Md r In these chemical formulas, Ma represents at least one element of metallic elements and metalloid elements that can form an alloy with lithium. Mb represents at least one element of metallic elements and metalloid elements other than lithium and Ma. Mc represents at least one element of nonmetallic elements. Md represents at least one element of metallic elements and metalloid elements other than Ma. And, s, t, u, p, q, and r satisfy s>0, t≧0, u≧0, p>0, q>0, and r≧0.
[0084] In addition, MnO2, V2O5, and V6O 13 Lithium (Li)-free inorganic compounds such as NiS, NiS, and MoS can be used.
[0085] Electrolytes: The electrolyte may be one or more of a gel electrolyte, a solid electrolyte, and an electrolyte solution, the electrolyte solution including a lithium salt and a non-aqueous solvent.
[0086] The lithium salt is one or more selected from the group consisting of LiPF6, LiBF4, LiAsF6, LiClO4, LiB(C6H5)4, LiCH3SO3, LiCF3SO3, LiN(SO2CF3)2, LiC(SO2CF3)3, LiSiF6, LiBOB, and lithium difluoroborate. For example, LiPF6 is selected as the lithium salt because it has high ionic conductivity and can improve cycle characteristics.
[0087] The non-aqueous solvent may be a carbonate ester compound, a carboxylate compound, an ether compound, another organic solvent, or a combination thereof.
[0088] The carbonate ester compound may be a chain carbonate ester compound, a cyclic carbonate ester compound, a fluorocarbonate ester compound, or a combination thereof.
[0089] Examples of linear carbonate compounds are diethyl carbonate (DEC), dimethyl carbonate (DMC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), ethyl methyl carbonate (EMC), and combinations thereof. Examples of cyclic carbonate compounds are ethylene carbonate (EC), propylene carbonate (PC), butylene carbonate (BC), vinyl ethylene carbonate (VEC), and combinations thereof. Illustrative examples of fluorocarbonate compounds are fluoroethylene carbonate (FEC), 1,2-difluoroethylene carbonate, 1,1-difluoroethylene carbonate, 1,1,2-trifluoroethylene carbonate, 1,1,2,2-tetrafluoroethylene carbonate, 1-fluoro-2-methylethylene carbonate, 1-fluoro-1-methylethylene carbonate, 1,2-difluoro-1-methylethylene carbonate, 1,1,2-trifluoro-2-methylethylene carbonate, trifluoromethylethylene carbonate, and combinations thereof.
[0090] Illustrative examples of carboxylate compounds are methyl acetate, ethyl acetate, n-propyl acetate, tert-butyl acetate, methyl propionate, ethyl propionate, propyl propionate, gamma-butyrolactone, decalactone, valerolactone, mevalonolactone, caprolactone, methyl formate, and combinations thereof.
[0091] Illustrative examples of ether compounds are dibutyl ether, tetraethylene glycol dimethyl ether, diethylene glycol dimethyl ether, 1,2-dimethoxyethane, 1,2-diethoxyethane, ethoxymethoxyethane, 2-methyltetrahydrofuran, tetrahydrofuran, and combinations thereof.
[0092] Examples of other organic solvents are dimethylsulfoxide, 1,2-dioxolane, sulfolane, methylsulfolane, 1,3-dimethyl-2-imidazolidone, N-methyl-2-pyrrolidone, formamide, dimethylformamide, acetonitrile, trimethyl phosphate, triethyl phosphate, trioctyl phosphate, phosphate esters, and combinations thereof.
[0093] The electrochemical device of the present invention includes all devices in which electrochemical reactions occur, and specific examples thereof include all kinds of primary batteries, secondary batteries, fuel cells, solar cells, and capacitors. In particular, the electrochemical device is a sodium secondary battery, a lithium secondary battery, or a polymer secondary battery.
[0094] The present invention further provides an electronic device comprising an electrochemical device according to the present invention.
[0095] The application of the electrochemical device of the present invention is not particularly limited, and can be used in any electronic device known in the prior art.In some embodiments, the electrochemical device of the present invention can be used in, but is not limited to, notebook computers, pen-input personal computers, mobile personal computers, electronic book players, mobile phones, mobile fax machines, mobile copiers, mobile printers, headphone stereos, video recorders, liquid crystal televisions, portable cleaners, portable CD players, minidisks, transceivers, electronic notebooks, calculators, memory cards, portable tape recorders, radios, backup power sources, motors, automobiles, motorcycles, power-assisted bicycles, bicycles, lighting equipment, toys, game machines, clocks, power tools, strobes, cameras, large-scale household storage batteries, and capacitors.
[0096] Hereinafter, the preparation of a lithium ion battery will be described with reference to specific examples, taking a lithium ion battery as an example. Those skilled in the art should understand that the preparation methods described in the present invention are merely exemplary, and any other suitable preparation methods are within the scope of the present invention.
[0097] Working Example: In the following, examples and comparative examples of the lithium ion battery according to the present invention will be described and performance evaluation will be performed.
[0098] 1. Preparation of lithium-ion batteries 1. Preparation of binder The preparation process of the acrylic binder was as follows: 1. An appropriate amount of acrylic acid monomer was added to the reaction kettle, and an appropriate amount of catalyst was added and stirred uniformly at low speed. 2. An appropriate amount of sulfonic acid group-containing monomer or carboxyl group-containing monomer (e.g., methylpropanesulfonic acid or methacrylic acid) was added to the reaction kettle. 3. An inert gas was introduced into the reaction kettle to form a reaction protection atmosphere. 4. The reaction kettle was heated to the reaction temperature to polymerize the monomer, and at the same time, a binder containing two functional groups was obtained. 5. After the reaction was completed, a metal base was added to adjust the discharge pH of the binder to obtain the desired binder. Here, binders containing different functional groups can be obtained by changing the type of reactive monomer. By selecting different types of metal bases (e.g., sodium hydroxide, magnesium hydroxide) or adding metal bases at different contents, the type and content ratio of metal bases in the binder can be designed and controlled. The preparation process of the cellulose-based binder was as follows: 1. Put an appropriate amount of raw cellulose into the reaction vessel, then add a metal base (sodium hydroxide) to basify the cellulose, and obtain basified cellulose; 2. Add an appropriate amount of chloroacetic acid to the basified cellulose to carry out an etherification reaction, and finally obtain sodium cellulose binder. Here, during the basifying treatment, the type and content ratio of the metal base in the binder can be designed and controlled by changing the relevant process parameters such as the type of metal base and the proportion of the metal base.
[0099] 2. Preparation method of separator After the water and inorganic particles were thoroughly mixed, a certain amount of binder was further added and the mixture was placed in a stirrer and stirred uniformly. Then, a certain amount of wetting agent was added to the slurry and the mixture was stirred until it was uniformly mixed. Finally, the mixture was uniformly coated on one side of the PE substrate to an appropriate thickness, and after the coating was completed, the mixture was dried in an oven to obtain the separator of the present invention. Here, the details of the parameters such as the components, contents, and coating thickness of the inorganic particles, binder, and wetting agent are shown in Table 1.
[0100] 3. Lithium-ion battery manufacturing method The positive electrode active material, lithium cobalt oxide, conductive carbon (Super P), and binder, polyvinylidene fluoride (PVDF), were dissolved in N-methylpyrrolidone solvent in a weight ratio of 96:2:2 and thoroughly mixed to prepare a positive electrode slurry. The positive electrode slurry was coated on aluminum foil, dried, cold pressed, and stripped to obtain a positive electrode. The negative electrode active material, artificial graphite, conductive agent (Super P), binder, styrene butadiene rubber, and thickener, sodium carboxymethyl cellulose, were dissolved in a deionized water solvent system in a weight ratio of 98:0.5:1:0.5, and thoroughly mixed to prepare a negative electrode slurry. The negative electrode slurry was coated on copper foil, dried, cold pressed, and stripped to obtain a negative electrode. A solution containing a lithium salt, LiPF6, and a non-aqueous organic solvent (ethylene carbonate (EC): diethyl carbonate (DEC): propylene carbonate (PC): propyl propionate (PP): vinylene carbonate (VC) = 20:30:20:28:2, mass ratio) in a mass ratio of 8:92 was used as the electrolyte for the lithium ion battery. The positive electrode, the separator, and the negative electrode were stacked in this order so that the separator was interposed between the positive electrode and the negative electrode, and then wound to obtain an electrode assembly. The electrode assembly was placed in an outer casing, an electrolyte was injected, sealed, and then formation was performed to manufacture the final lithium-ion battery product.
[0101] 2.Measurement method 1. Separator perforation measurement First, the separator including the porous coating layer was fixed flat on a measuring jig, and the jig was placed vertically below the moving bracket of a Gotech tensile tester (Gotech Testing Machines Inc.). Next, the heated needle used during the measurement was fixed vertically on the moving bracket of the Gotech tensile tester to ensure that the heated needle penetrated the separator vertically. Then, the moving bracket of the Gotech tensile tester moved the heated needle at a constant speed (20 cm / min) to penetrate the separator vertically, and the penetration depth was 2 to 4 cm. After piercing, the heated needle stopped for 1 minute and then returned to the initial position. Finally, the separator sample was taken out, and under the CCD camera, any two points on the edge of the rupture hole were connected, and the distance between the two points was calculated, and the maximum value was taken as r.
[0102] 2. Measurement of compressive strength of binder A binder adhesive film sample (size: 10mm x 10mm x 10mm) was placed in the center of two pressure plates of a universal testing machine, and stress was applied at a constant speed (10mm / min) along the vertical direction of both end faces of the sample to compress the sample, and the sample was compressed and deformed so that it shortened in the axial direction and expanded in the radial direction until it was broken. The maximum load stress value Pmax by the universal testing machine was read, and the compressive strength α of the binder was calculated using the following formula.
number
[0103] 3. Measurement of the glass transition temperature of the binder A certain amount (10-20mg) of the binder adhesive film sample was taken and placed in the crucible of the differential scanning calorimeter. The test program of the instrument was started, and the Temp-DSC curve was obtained by the measurement software. The temperature corresponding to the first change stage of the curve was usually read as the glass transition temperature of the binder.
[0104] 4. Measurement of metal elements and their content ratio in binder The battery was placed in a glove box and disassembled, the separator was removed, and the PVDF / PMMA adhesive layer coated on the porous coating layer was removed, leaving the porous coating layer. The porous coating layer was then redispersed in water using the "water washing" method, and the inorganic particles were centrifuged to obtain a water washing solution containing the binder. The water washing solution was measured using an inductively coupled plasma (ICP) test to determine the metal elements and their content in the binder.
[0105] 5. Measurement of the specific surface area of inorganic particles The measurement software was started, a certain amount of inorganic particles was placed in the sample measurement chamber, and the specific surface area of the inorganic particles was measured using the BET specific surface area measurement method. After the measurement was completed, the measurement software automatically read the value of the specific surface area of the inorganic particles.
[0106] 6. Measurement of particle size of inorganic particles The measurement software was started, inorganic particles that met the measurement quality requirements were placed in the measurement chamber of the Malvern3000 laser particle size analyzer, and then ultrasonic was turned on to ensure that the particles were not aggregated by ultrasonication for 5 minutes. Then, the particle size measurement step was entered, and the particle size distribution curve was output by the software.
[0107] 7. Measurement of thermal shrinkage of separator in MD and TD directions First, the separator was cut to a size of length MD1 and width TD1 (MD1 = 10 cm, TD1 = 5 cm) to obtain a separator sample for measurement. Next, the cut separator sample was sandwiched between two sheets of A4 paper and baked in an oven at 150 ° C for 1 hour. After that, the length and width of the separator sample after baking at 150 ° C for 1 hour were measured with a CCD camera and recorded as MD2 and TD2, respectively. Finally, the thermal shrinkage rate L1 in the MD direction of the separator and the thermal shrinkage rate L2 in the TD direction of the separator were calculated by the following formula.
[0108]
number
[0109] 8. Measurement of the thickness of the porous coating layer The thicknesses of the substrate and separator were measured with a benchtop separator thickness gauge and recorded as T1 μm and T μm, respectively. The thickness of the porous coating layer, T2 μm, was calculated by the following formula:
number
[0110] 9. Measurement of adhesion strength of porous coating layer First, the coated separator sample was placed flat on a glass plate with the porous coating layer facing up and the four sides were fixed with tape to ensure that the separator was fixed flat on the glass plate. Next, the peel force measurement tape was applied flat on the surface of the porous coating layer. Then, a 1KG pressure roller was used to roll the area where the peel force measurement tape was applied back and forth. Then, a separator measurement sample of 15mm x 54.2mm was cut out from the area where the peel force measurement tape was applied. Finally, the separator measurement sample side was fixed to one end of a Gotech tensile tester and the tape side was fixed to one end of the moving bracket of the Gotech tensile tester, and the moving bracket pulled the tape at a constant speed to peel the tape 180° from the surface of the separator, and the value read by the measurement software was taken as the adhesion strength of the porous coating layer.
[0111] 10. Hot box measurement 100 lithium-ion battery samples were taken and charged at a constant current of 0.5C to 4.5V at room temperature, then charged at a constant voltage of 4.5V until the current became less than 0.05C, and then fully charged to 4.5V. The lithium-ion battery samples were placed in an oven and left at 137°C for 1 hour. If the lithium-ion battery did not emit smoke, fire, or explode, it was recorded as passing, otherwise it was recorded as failing. The hot box passing rate refers to the ratio of the number of lithium-ion batteries that passed the test to the total number of lithium-ion batteries.
[0112] 11. Nail penetration measurement First, the appearance of the battery was inspected and photographed before the nail penetration test. Then, a temperature sensor wire was attached to the center of the battery surface. After that, in a measurement environment of 20±5℃, the battery to be measured was placed on the surface of the test bench, and a steel nail with a diameter of 2.5 mm was used to measure at the center of the sample at a speed of 150 mm / s, completely piercing the sample. If the battery did not ignite or explode, it meant that the battery passed the test.
[0113] 3. Measurement results Table 1 shows the effect of the pH value and content of the binder on the properties of the binder, the properties of the separator, and the electrochemical properties. As can be seen from Table 1, compared with the comparative example, the first binder and the second binder are simultaneously adopted in the embodiment, and the pH values and contents of the first binder and the second binder are simultaneously adjusted to satisfy 7≦pH1≦11, 3≦pH2≦7, 0.5≦w1≦4, 2.5≦w2≦5, so that the embodiment can achieve the following effects: (1) a binder with high compressive strength and high Tg temperature is obtained; (2) after baking at 150℃ for 1 hour, the separator in the embodiment has lower MD and TD thermal shrinkage and smaller rupture holes in the hot drilling test; and (3) the electrochemical equipment in the embodiment all pass the hot box test and the nail penetration test.
[0114] Table 2 is an improvement based on Example 1-1, in which the total content of the added first binder and second binder is similar, and the only difference is the content ratio of the first binder to the second binder. As can be seen from the data in Table 2, by further adjusting the content ratio w1 / w2 of the first binder to the second binder to satisfy 0.2≦w1 / w2≦1.6, the tensile strength of the binder, the thermal stability of the separator, and the safety properties of the electrochemical device can be further improved.
[0115] Table 3 is an improvement based on Example 1-1, and the total charge content of the metal elements added to the first binder is similar (i.e., one acid group (carboxyl group / sulfonic acid group) in the first binder reacts with one metal ion whose valence is +1, and the others can be inferred from this), and the only difference is the type and content ratio of the added metal elements. As can be seen from the data in Table 3, compared with the case where only one metal element is added, after adding two metal elements to the first binder, the compressive strength of the binder, the thermal stability of the separator, and the safety properties of the electrochemical device are all further improved.
[0116] Furthermore, as can be seen from Examples 3-6 to 3-15, when the content ratio a of the metal element having a valence of +1 to the metal element having a valence of +2 is within the range of 1≦a≦10, the properties of the binder, separator, and electrochemical device can be further improved. As can be seen from Examples 3-16 to 3-20, when the content ratio b of the metal element having a valence of +1 to the metal element having a valence of +3 is within the range of 1≦b≦50, the properties of the binder, separator, and electrochemical device can be further improved.
[0117] Table 4 is an improvement based on Examples 3-7, and the only difference is the composition of inorganic particles, the median diameter of inorganic particles, and the content of inorganic particles. As can be seen from Examples 3-7 to 4-5, by selecting aluminum oxide, boehmite, zirconia, boron nitride, silicon nitride, or aluminum nitride as the inorganic particles in the porous coating layer, a separator and an electrochemical device with excellent high-temperature properties can be obtained.
[0118] As can be seen from Examples 4-6 to 4-12, when the median diameter Dv50 of the inorganic particles satisfies 0.3 μm≦Dv50≦2 μm, a separator and an electrochemical device with more excellent high-temperature properties can be obtained.
[0119] As can be seen from Examples 4-13 to 4-16, when the content m1 by weight of the inorganic particles relative to the total weight of the porous coating layer satisfies 90≦m1≦96, a separator and an electrochemical device with superior high-temperature properties can be obtained.
[0120] Table 5 is an improvement based on Examples 3-7, and the only difference is the composition of the wetting agent and the content of the wetting agent. As can be seen from Table 5, by selecting polyoxyethylene alkylphenol ether, polyoxyethylene aliphatic alcohol ether, polyoxyethylene polyoxypropylene block copolymer, or siloxane as the wetting agent in the porous coating layer, a separator and an electrochemical device with excellent high-temperature properties can be obtained.
[0121] As can be seen from Examples 5-3 to 5-7, when the content m3 by weight of the wetting agent relative to the total weight of the porous coating layer satisfies 0.5≦m3≦1.5, a separator and an electrochemical device having more excellent high-temperature properties can be obtained.
[0122] Table 6 is an improvement based on Examples 4-6, and the only difference is the thickness of the porous coating layer. As can be seen from Table 6, when the thickness T of the porous coating layer is within the range of 0.5≦T≦3, a separator and an electrochemical device with better high-temperature properties can be obtained.
[0123] Throughout the specification, references to "an embodiment," "some of the embodiments," "one embodiment," "another example," "example," "embodiment," or "some of the examples" mean that at least one embodiment or example of the invention includes the particular feature, structure, material, or characteristic described in that embodiment or example. Thus, the appearances of, for example, "in some embodiments," "in an embodiment," "in another example," "in one example," "in a particular example," or "example" in various places throughout the specification do not necessarily refer to the same embodiment or example of the invention. Furthermore, the particular features, structures, materials, or characteristics herein may be combined in any suitable manner in one or more embodiments or examples.
[0124] Although illustrative embodiments have been disclosed and described, those skilled in the art should understand that the above-described embodiments are not to be construed as limiting the invention, and that modifications, substitutions, and alterations to the embodiments are possible without departing from the spirit, principles, and scope of the invention.
[0125] [Table 1] JPEG2025514841000009.jpg24896
[0126] [Table 1 - continued] JPEG2025514841000010.jpg24468 JPEG2025514841000011.jpg240156
[0127] [Table 2]
[0128]
Table 3
[0129]
Table 4
[0130]
Table 5
[0131]
Table 6
Claims
1. A separator, A porous substrate and a porous coating layer, The porous coating layer is provided on at least one surface of the porous substrate, The porous coating layer comprises inorganic particles and a binder; the binder comprises a first binder, The first binder contains a metal element, A needle having a diameter R and a round tip heated to 500° C. is used to perform thermal piercing on the separator, a rupture hole is obtained in the separator, two arbitrary points on the edge of the rupture hole are connected, and the distance between the two points is calculated, and the maximum value is r; A separator, wherein R and r satisfy 400 μm≦R≦1000 μm and 0.9≦r / R≦5.
2. The separator according to claim 1 , wherein r satisfies 400 μm≦r≦1500 μm.
3. The separator according to claim 1 , wherein α satisfies 0.5≦α≦10, where α is a compressive strength of the binder in MPa.
4. The separator according to claim 1 , wherein the binder has a glass transition temperature Tg, which satisfies 150° C.≦Tg≦300° C.
5. 2. The separator according to claim 1, wherein the metal element comprises at least one of metal elements having a valence of +1, +2, or +3.
6. 2. The separator according to claim 1, wherein the metal element includes at least two of the metal elements having a valence of +1, +2, or +3.
7. The first binder is (a) the metal element having a valence of +1 includes at least one of Li and Na; (b) the metal element having a valence of +2 includes at least one of Ca and Mg; (c) the metal element having a valence of +3 includes Al; The separator according to claim 1 , which satisfies at least one of the above.
8. The binder is (d) when the molar content ratio of the metal element having a valence of +1 to the metal element having a valence of +2 is a, a satisfies 1≦a≦10; (e) when the molar content ratio of the metal element having a valence of +1 to the metal element having a valence of +3 is b, b satisfies 1≦b≦50; The separator according to claim 1 , which satisfies at least one of the above.
9. The first binder contains at least one of a carboxyl group and a sulfonic acid group, and the pH value of the first binder is adjusted to pH 1 When the pH is 1 pH 7≦ 1 The separator according to claim 1 , wherein the separator satisfies ≦11.
10. 2. The separator of claim 1, wherein the first binder comprises at least one of sodium polymethylcellulose, lithium polymethylcellulose, lithium polycarboxymethylcellulose, lithium polyhydroxypropylmethylcellulose, calcium polyacrylate, lithium polyacrylate, and calcium polymethacrylate.
11. The binder further comprises a second binder; 2. The separator according to claim 1, wherein β, a weight ratio of the first binder to the second binder with respect to a total weight of the porous coating layer, satisfies 0.2≦β≦4.
12. The second binder contains at least one of a carboxyl group and a sulfonic acid group, and the pH value of the second binder is adjusted to pH 2 When the pH is 2 pH 3≦ 2 The separator according to claim 11, wherein the separator satisfies ≦7.
13. 12. The separator of claim 11, wherein the second binder comprises at least one of polybutyl acrylate, polyethyl acrylate, polybutyl methacrylate, polymethyl methacrylate, and styrene butadiene rubber.
14. The specific surface area of the inorganic particles is S BET m 2 / g, S BET 2≦S BET The separator according to claim 1 , wherein the separator satisfies ≦10.
15. The separator according to claim 1 , wherein the particle diameters Dv50 and Dv99 of the inorganic particles satisfy 0.3 μm≦Dv50≦3 μm and Dv99≦4 μm, respectively.
16. The separator according to claim 1 , wherein the inorganic particles include at least one of aluminum oxide, boehmite, zirconia, boron nitride, silicon nitride, and aluminum nitride.
17. The porous coating layer further comprises a wetting agent; 2. The separator according to claim 1, wherein, when a content of the inorganic particles is m1 weight %, a content of the binder is m2 weight %, and a content of the wetting agent is m3 weight %, relative to a total weight of the porous coating layer, m1, m2, and m3 satisfy 90≦m1≦96, 3≦m2≦9, 0.5≦m3≦2, and m1+m2+m3=100.
18. 18. The separator of claim 17, wherein the wetting agent comprises at least one of polyoxyethylene alkylphenol ethers, polyoxyethylene aliphatic alcohol ethers, polyoxyethylene polyoxypropylene block copolymers, and siloxanes.
19. 2. The separator according to claim 1, wherein when the separator is left at 150° C. for 1 hour, a heat shrinkage rate of the separator in a longitudinal MD direction is L1 and a heat shrinkage rate of the separator in a widthwise TD direction is L2, compared to the initial length and width of the separator, L1 and L2 satisfy L1<10%, L2<10%, and 0.75≦L1 / L2≦1.
2.
20. The separator according to claim 1 , wherein when the thickness of the porous coating layer is T μm, T satisfies 0.5≦T≦3.
21. The separator according to claim 1 , wherein when the adhesive strength of the porous coating layer is F N / m, F satisfies 5≦F≦100.
22. An electrochemical device comprising the separator according to any one of claims 1 to 21.
23. 23. An electronic device comprising the electrochemical device of claim 22.
Citation Information
Patent Citations
Modified ceramic separator composite and method for producing the same
JP2018528583A
Separator for lithium ion secondary battery
JP2021057236A